Point‐of‐care diagnosis of invasive aspergillosis in non‐neutropenic patients: Aspergillus Galactomannan Lateral Flow Assay versus Aspergillus‐specific Lateral Flow Device test in bronchoalveolar lavage. Issue 3 (15th January 2019) - Jenks, Jeffrey D.; Mehta, Sanjay R.; Taplitz, Randy; Aslam, Saima; Reed, Sharon L.; Hoenigl, Martin
Summary: Background: We compared new Aspergillus Galactomannan Lateral Flow Assay with the newly formatted Aspergillus‐ specific Lateral Flow device tests for the diagnosis of invasive pulmonary aspergillosis (IPA) in non‐neutropenic patients. Methods: We performed both tests in 82 bronchoalveolar lavage fluid samples from 82 patients at risk for IPA but without underlying haematologic malignancy. Samples were collected between September 2016 and September 2018 at the University of California San Diego, United States. IPA was classified following two published consensus criteria. Results: Classification of cases varied widely between the two consensus criteria. When using criteria established for the intensive care unit, 26/82 patients (32%) met criteria for proven or putative IPA. Both point‐of‐care assays showed sensitivities ranging between 58% and 69%, with specificities between 68% and 75%. Sensitivity increased up to 81% when both tests were combined. Conclusion: The study outlines the need for updated, unified and more broadly applicable consensus definitions for classifying IPA in non‐neutropenic patients, a work that is currently in progress. Both point‐of‐care tests showed comparable performance, with sensitivities and specificities in the 60%‐70% range when used alone and increasing to 80% when used in combination. The new point‐of‐care tests may serve a role at the bedside in those with clinical suspicion of IPA.